Peranan Daerah Perkotaan Bagi Pembangunan Regional: Penerapan Model Thunen Yang Dimodifikasikan Di Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRAK Location theory shows how firms at first choose their respective optimal local and finally decide to locate in the same area (with the lowest isodapane) so that it f a city, which is something that has to happen when firms want to operate efficiently profitably. Further, von Thursen's concentric zone model shows that the determinants land rent (level of development) are the size of an urban area and accessibility to urban area. The size of an urban area has a positive effect on the level of develop whereas the accessibility has negative effect on the level of development. application of that model to the US. economy has supported the expectation that areas and accessibility influence the level of development. The results of applying Thunen model to the Indonesian economy will indicate whether the number olcities the sizes of cities and the number and types of roads/highways in Indonesia are optimal or not so that the national urban development strategy in Indonesia needs to revised or not.